Islamic Branding: Insights from Strengthening Madrasah Competitiveness in Building Public Trust - Ghufron, Ghufron; Khusnurridlo, Moh; Najiburrahman, Najiburrahman; Baharun, Hasan; Muchlis, Moh Najib Hasbullah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the madrasah branding strategy in increasing the competitiveness of institutions to win the competition between educational institutions. This study uses a qualitative approach to the type of case study. Data collection techniques are carried out through observation, interviews and documentation. The data analysis was carried out circularly, starting from data collection, reduction, data display and conclusion. The results show that madrasah branding in increasing the competitiveness of its institutions is carried out through continuous planning, implementation and evaluation by involving all madrasah residents to be involved in realizing shared goals by utilizing various available platforms. This research has implications for the importance of being involved in totality to design and implement a program to achieve the desired targets optimally.